Modelling and simulating coral impacts by chemical pollutants in coral atolls : applications of CEMOS and WINTOX in coral reefs - 214811 Mustafa Kamal Abdul Aziz; Sabariah Mohd. Yunus; Zool Fadly Naharuddin; Abdul Wahab Abdullah; International Freshwater Management Conference (2003 : Kuching Sarawak) (Skudai : Universiti Teknologi Malaysia, 2003)
42